Tert Deletion Impairs Circadian Regulation of Blood Pressure in Male Spontaneously Hypertensive Rats - Semenovykh, Kateryna; Pravenec, Michal; Vaněčková, Ivana; Houdek, Pavel; Sládek, Martin; Šimáková, Miroslava; Mlejnek, Petr; Selvi, Saba; Šilhavý, Jan; Liška, František; Semenovykh, Dmytro; Hojná, Silvie; et al. (Hypertension (Dallas, Tex., 2026)
BACKGROUND: Deletion of the Tert gene leads to telomere shortening, which is associated with aging and age-related cardiovascular disease, but its effects on circadian regulation of blood pressure have not yet been investigated. To fill this gap, we developed a rat model with genetic deletion of the Tert gene on a spontaneously hypertensive rat-Tert-/- background, in which telomeres were shortened in the F3 generation. METHODS: We analyzed the effects of Tert deletion on locomotor activity, oxidative stress, telemetrically measured parameters of the cardiovascular system, and the expression of clock genes in various tissues. RESULTS: Male spontaneously hypertensive rat-Tert-/- showed a reduced physical fitness, which was reflected in a more fragmented nocturnal activity and a poorer correlation between spontaneous activity and cardiovascular parameters. Day/night blood pressure amplitude was reduced, and the circadian rhythm of systolic blood pressure was completely abolished in constant darkness. In the rostral ventromedial medulla of the brainstem, the number of TH (tyrosine hydroxylase)-immunopositive cells was reduced, indicating a decrease in sympathetic tone. In heart tissue, the level of protein oxidation was increased, and similar to other tissues, the day/night expression of clock genes was significantly changed, suggesting an impairment of the synchrony of their clocks. CONCLUSIONS: Our results suggest that deletion of Tert impairs circadian regulation of blood pressure via a decreased rhythm of sympathetic activity innervating the heart and other tissues, leading to impaired circadian regulation of local peripheral clocks. These findings provide a possible link between age-related telomere shortening and impaired rhythmicity of cardiovascular function.
Keywords: blood pressure; Disease Models, Animal; circadian clocks; heart rate; zvířata; oxidační stres; krevní tlak; Gene Deletion; rats; Male; mužské pohlaví; hypertenze; Animals; telomerasa; Blood Pressure; delece genu; krysa rodu Rattus; Telomere Shortening; Hypertension; Oxidative Stress; Rats; modely nemocí na zvířatech; zkracování telomer; Rats, Inbred SHR; Circadian Rhythm; Telomerase; potkani inbrední SHR; cirkadiánní rytmus; oxidative stress